Current-controlled nickel-catalyzed multi-electrophile electroreductive cross-coupling. Issue 4 (31st January 2023) - Xie, Shentong; Yin, Yuqing; Wang, Ya; Wang, Jiannan; He, Xiaoqian; Bai, Ruopeng; Shi, Renyi
Abstract : The electroreductive cross-electrophile coupling which has emerged as a powerful, green and efficient method for constructing challenging C–C bonds has attracted increasing attention from organic chemists. Abstract : The electroreductive cross-electrophile coupling which has emerged as a powerful, green and efficient method for constructing challenging C–C bonds has attracted increasing attention from organic chemists. Most of the previous works focus on direct two-electrophile cross-coupling. In this work, the nickel-catalyzed three-electrophile electroreductive cross-electrophile coupling which offers direct convergent synthesis to target molecules from easily-available and cheap substrates has been developed. A wide range of alkyl aryl ketones are accessed from alkyl halides, aryl iodides and propyl chloroformate under mild conditions, avoiding the use of over-stoichiometric reductants, excess quantities of additives and activators, and superstoichiometric CO gas or metal carbonyl complexes which are toxic, environmentally unfriendly and can be inconvenient to handle. The scale-up experiment indicates the good scalability of electrosynthesis compared to traditional synthesis. High chemo-selectivity can be achieved through an increase in the current. Mechanistic investigation suggests that the electron transfer rate from the cathode to Ni catalysts plays a vital role in this protocol. Our approach demonstrates a novel electrochemical selectivity-controlled strategy in cross-electrophile coupling.